Acute renal failure due to severe hypercalcemia and nephrocalcinosis treated with two doses of pamidronate in an infant with Williams-Beuren syndrome - Baştuğ, Funda; Nalçacıoğlu, Hülya; Baş, Veysel Nijat; Tekatlı-Çelik, Binnaz; Çetinkaya, Hasan; Yel, Sibel (The Turkish Journal of Pediatrics, 2018)
Infantile hypercalcemia has been reported in 15% of infants and children with Williams-Beuren syndrome (WBS) and has generally mild clinical symptoms. However, the need for pamidronate treatment in a few infants with severe hypercalcemia associated with WBS has been reported in literature. Many disorders, such as primary hyperoxaluria, associated with nephrocalcinosis can lead to renal failure, but there are only a few reports in infants with WBS who have decreased renal function and nephrocalsinosis. We present a 23-month-old girl with WBS (confirmed with fluorescent in situ hybridization probes) who presented with acute renal failure with severe symptomatic hypercalcemia and nephrocalcinosis, which responded to two infusions of pamidronate.